LPG2 Gene Duplication in Leishmania infantum: A Case for CRISPR-Cas9 Gene Editing - Jesus-Santos, Flávio Henrique; Lobo-Silva, Jéssica; Ramos, Pablo Ivan Pereira; Descoteaux, Albert; Lima, Jonilson Berlink; Borges, Valéria Matos; Farias, Leonardo Paiva (Frontiers in Cellular and Infection Microbiology, 2020)
On the surface of the Leishmania promastigote, phosphoglycans (PG) such as lipophosphoglycan (LPG), proteophosphoglycan (PPG), free phosphoglycan polymers (PGs), and acid phosphatases (sAP), are dominant and contribute to the invasion and survival of Leishmania within the host cell by modulating macrophage signaling and intracellular trafficking. Phosphoglycan synthesis depends on the Golgi GDP-mannose transporter encoded by the LPG2 gene. Aiming to investigate the role of PG-containing molecules in Leishmania infantum infection process, herein we describe the generation and characterization of L. infantum LPG2-deficient parasites. This gene was unexpectedly identified as duplicated in the L. infantum genome, which impaired gene targeting using the conventional homologous recombination approach. This limitation was circumvented by the use of CRISPR/Cas9 technology. Knockout parasites were selected by agglutination assays using CA7AE antibodies followed by a lectin (RCA 120). Five clones were isolated and molecularly characterized, all revealing the expected edited genome, as well as the complete absence of LPG and PG-containing molecule expression. Finally, the deletion of LPG2 was found to impair the outcome of infection in human neutrophils, as demonstrated by a pronounced reduction (~83%) in intracellular load compared to wild-type parasite infection. The results obtained herein reinforce the importance of LPG and other PGs as virulence factors in host-parasite interactions.